Urinary tract - Anderson, Karl-Erik; Michel, Martin C. (Handbook of experimental pharmacology, 2011)
The basic anatomy and physiology of the urinary tract, the validity of animal models and other methodological considerations as well as a range of potential therapeutic targets are comprehensively reviewed by leading international experts, making this a unique reference source for basic scientists and research-minded clinicians alike.